Meaning-of-life orientations and values in youth in the period of familial relationships formation - Жанна Ю. Кара; Людмила Ю. Крутелева (Rossijskij psihologičeskij žurnal., 2020)
Introduction. The article is dedicated to values and life meanings in the young people in course of familial relationships formation. The relevance of the topic results from the interest in the relationship of young people, in their building of their own personal life course. The study aims to study the value-meaning characteristics of young people married or searching partners. 61 subjects have been enrolled in the study, aged 18 to 35 years. The authors compared values and life-meanings in youths being married or seeking for a partner. Methods. Comparative analysis and generalization of theoretical principles were applied; diagnostic techniques were also used: the “System of life meanings technique”, “Schwartz’s Values Survey”, “Questionnaire of self-relation”; Methods of mathematical processing of empirical data: to analyze the main characteristics of the distribution, we used descriptive statistics and the Mann–Whitney U-test. Results and Discussion. In the group of young men looking for a partner, preferred life meanings were such as searching for life purpose, existential understanding of the one’s being, one’s place in the society, self-development and self-realization, active interactions with other people. For the married youth, the value “self-development” was not relevant, what could influence the family integrity, according to authors. Significant values for the married young people were personal safety, protection against external conditions, a tendency towards achievements within the personal or professional field. For the young people looking for a partner, important values were achievement as the evidence of personal growth, self-sufficiency as acceptance, and responsibility for oneself and one’s life. Statistically significant interrelations between values and life meaning in the youth in a period of the familial relationships formation are presented. The study is novel in that it revealed and characterized the life meanings and values of the modern youth, married or looking for a partner.